Diversity of endophytic actinobacteria isolated from medicinal plants and their potency as pancreatic lipase inhibitor - LENNI FITRI (Society for Indonesian Biodiversity, 2017)
Fitri L, Meryandini A, Iswantini D, Lestari Y. 2017. Diversity of endophytic actinobacteria isolated from medicinal plants and their potency as pancreatic lipase inhibitor. Biodiversitas 18: 857-863. Endophytic actinobacteria from medicinal plants have high diversity and potency to produce secondary metabolites with various biological functions, including the activity of lipase inhibitor. As it has been widely known that inhibiting fat absorption through the activity of pancreatic lipase inhibitor is one of the most common treatments for weight loss. This study aimed to assess diversity and capability of endophytic actinobacteria in producing pancreatic lipase inhibitor from medicinal plants that were traditionally used as antiobesity. Medicinal plants used in this research were rhizome of Alpinia galanga, Kaempferiae galanga, K. rotunda, Zingiber cassumunar, and leaves of Murraya paniculata. The endophytic actinobacteria were isolated, purified, and assayed for lipase inhibitory activity. The selected isolates were molecularly identified based on 16S rRNA gene and compared for their close relationship with reference strains available in the GenBank. A total of 35 endophytic actinobacteria has been isolated from the five medicinal plants examined. The isolates showed to have various morphological diversity based on their colony and microscopic observations, and also to have various lipase inhibitory activity. The inhibition activity ranged from 6.1 to 96.5%. There were five selected endophytic actinobacteria which have lipase inhibitory activity higher than 90%. At the same concentration of sample (1300 ppm), the crude extract of AEBg12 showed slightly higher activity (95.3%) compared with orlistat (93.6%), used as a positive control. The partial sequences of 16S rRNA analyses showed that AEBg4 (1421 bp) had the highest similarity with Streptomyces sp. S170 (93%), followed by its close relationship with S. lannensis strain SR3-58 (93%), and S. lannensis JCM 16578T (92%). Both AEBg10 (1051 bp) and AEBg12 (1010 bp) had the highest similarity with Streptomyces sp. S170 by 99% and 98%, respectively. The AEKp9 (1367 bp) had a close relationship with Streptomyces sp. DLDG2 (93%) and S. bellus NBRC 12844T (93%). While for AELk3 (1033 bp), the similarity with Streptomyces sp. NRLL B-24869 was 98%. These research data can be considered as new information, regarding the capability of endophytic actinobacteria from medicinal plants, which have potency as antiobesity, through their pancreatic lipase inhibitory activity.